Minimal non-PC-groups - Artemovych, O.D. (Algebra and Discrete Mathematics, 2014)
The purpose of this paper is to prove that a non-perfect group G is a minimal non-PC-group if and only if it is a minimal non-FC-group. It is shown that a perfect locally graded minimal non-PC-group is an indecomposable countable locally finite p-group.